Optimasi Sistem HVAC di Gedung UMKM 3 Lantai Universitas Sumatera Utara Menggunakan Pipe Flow Expert untuk efisiensi energi dan pengurangan Head Loss - Nasution, Arif Fadillah (universitas teuku umar, 2024)
Heating, ventilation, and air conditioning (HVAC) systems are essential for ensuring comfort and energy efficiency. Due to high head loss in the HVAC piping system, the three-story SME building faces energy efficiency issues, leading to increased energy consumption and operational costs. Using Pipe Flow Expert software, this study aims to optimize the SME building’s HVAC system to conserve energy. The main goal of this research is to reduce energy consumption and operational costs by decreasing head loss within the piping network and improving pump efficiency. To achieve head loss reduction and decrease system power requirements, this study utilized Pipe Flow Expert simulations to test various piping configurations. Results show that pipes with smaller diameters and longer lengths tend to generate greater head loss, causing pumps to consume more power. Recommendations for modifying pipe diameter and selecting materials with lower roughness coefficients successfully reduced head loss by up to 30%, enabling pumps to operate more efficiently. A total power reduction from 5.96 kW to 4.172 kW was observed. This study concludes that optimizing piping systems and enhancing pump efficiency significantly improves the performance of HVAC systems in the SME building at Universitas Sumatera Utara. Additionally, this study provides a valuable contribution toward developing more efficient and environmentally friendly HVAC systems and can serve as a model for similar research and development in the future.